The Changing Role of Planners in Local Planning Practices: a Comparetive Analysis of Two Planning Studies of Izmir - Mert, Yelda; Kaya Erol, Nursen (Izmir Institute of Technology, 2009)
The main goal of this thesis is to understand the changing role of urban planners in a historical perspective. Moreover, the historical perspective of the role of planners is investigated parallel to the changes in planning. To understand the role of planners, especially in the planning practices of Turkey, the period before and after the 1980s are examined. Initially, planning theories and relevant theoretical studies as well as case studies from around the world are analyzed in terms of the role of planners. To understand the role of planners before and after the 1980s, two comprehensive planning studies are selected from İzmir, Turkey. One of them is the 1973 Master Plan prepared by İzmir Metropolitan Planning Office and the other is the 2007 Master Plan prepared by İzmir Metropolitan Municipality. The in-depth interview method with the planning staff is used as the methodology of the thesis.
Thesis (Master)--Izmir Institute of Technology, City and Regional Planning, Izmir, 2009
Includes bibliographical references (leaves: 96-105)
Text in English; Abstract: Turkish and English
x, 107 leaves
Keywords: HT169.T9 .M75 2009; City planning--Turkey--İzmir